Unwholesome Tendencies in the Judicial Appointment - A Nepali Perspective - Khanal, Bishal (Kathmandu School of Law Review, 2018)
Although judges are often examined and inspected on various court affairs and subsequent efficiency or deficiency, judge-making systems, especially supersession, is largely unchecked. Nonetheless, it comprises a huge ground for worrying domain of diminishing values and esteem of courts. Unfair practices in appointment and the way they are responded to, hugely embody devastating present and damaging future for expected strength in judiciary. This paper, besides citing various scholars’ views on how a judge should be, critically examines the tendency of Supersession (one of the wrong norms in judicature) and its impacts in eroding the efficacy of judiciary.